Wykorzystanie coachingu w codzienności szkolnej - Kozielska, Joanna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The intention of the author of the text is to present the terminological distinctions securing coaching in the right place in the face of the definition chaos that accompanies him. An example of a structured coaching conversation will be presented in the context of teaching a particular subject. In the remainder of the paper will illustrate the elements of the coach’s work for the daily use and the proficiency that this method can cause for participants in the education system with particular regard to the changes that can be made in the students.
Keywords: coaching; school; teacher